Techniques in Science Advice: Modelling for Policy and the Politics of Models (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Computational models have become indispensable in policy-making across many domains, from environmental regulation, to trade policies and public health. Yet their role as techniques in science advice remains underexplored. This article discusses models through three interrelated analytical dimensions: as boundary objects coordinating different social spheres; as sites where authority is enacted, negotiated, and contested; and as performative devices that actively constitute policy realities. Drawing on social science scholarship and empirical cases, the article demonstrates how models entangle epistemic, technical, social, and political dimensions within advisory assemblages. It concludes with a discussion of responsible modelling, emphasizing inclusion, transparency, and communication.
Keywords: computational models; science advice; boundary objects; authority; performative power